THE RIGHT TO DIE: THE CONFRONTATION OF HUMAN DIGNITY AND THE RIGHT TO LIFE (Interdisciplinary Studies Journal, 2025)
That the subject of death is a great social taboo in many societies, a large number of people, and especially the most vulnerable, do not have the privilege use contract doctor or nursing for they can have the end of life into their homes, accompanied by family members, without feeling pain, which transforms the theme of the end of life in a matter not only of ethical and moral relevance but also of social relevance. The sacrificed extension of the lives of incurable patients exposes human beings to humiliating situations of pain and suffering. Therefore, research is carried out on Dignant Death, to solve the problem that when there is no longer a dignified and full life, and it is proven that it is only possible to wait for death, the patient would have the right to exercise his autonomy, shortening the period of pain and anticipating death or should the State/Law must forced to maintain life at any price? Because of this, the objective was to conceptualize the themes of human dignity, and the autonomy of the will, as well as to explore the Theory of Weighting, applying the principles in a confrontation in the issue of a good death, which is life versus dignity, so that we could decide which should prevail and, finally, it was analyzed how the subject was treated in Brazilian legislation. To this end, predominantly bibliographical research was carried out based on a review of classic works and a survey of new works. In short, it was seen that a real possibility of legalizing of euthanasia in Brazil was glimpsed, leading to the conclusion about the topic that required us must be more widely discussed both in political institutions and in civil society.Keyword: Dignified death; Freedom of choice; Human Dignity; Fundamental Human Rights.
Keywords: Dignified Death; Autonomy of Will; Human Dignity; Fundamental Rights